HIGH-PRESSURE MINERALS IN MAFIC MICROGRANULAR ENCLAVES: EVIDENCES FOR CO-MINGLING BETWEEN LAMPROPHYRIC AND SYENITIC MAGMAS AT MANTLE CONDITIONS - Plá Cid J.; Nardi L.V.S.; Stabel L.Z.; Conceiçao R.V.; Balzaretti N.M. (My University, 2003)
Mafic microgranular enclaves, composed of diopside and rare magnesium biotite phenocrysts in a groundmass of diopside, biotite, apatite, Fe-Ti-oxides, and alkali feldspar, are associated with Neoproterozoic Piquiri potassic syenite in southern Brazil. Co-genetic mica and clinopyroxene cumulates present inclusions of pyrope-rich garnet in diopside phenocrysts. Textural evidence, as well as the chemical and mineralogical composition, suggest that enclaves crystallized from a lamprophyric magma and co-mingled with the host syenitic magma. The contrasting temperature between both magmas and the consequent chilling was important for the preservation of some early-crystallized minerals in the mafic magma. Diopside groundmass grains contain micro-inclusions of K-rich augite and phlogopite, and some clinopyroxene phenocrysts and elongate groundmass crystals have potassium-rich cores. The pyrope-rich garnet have high #mg number (67–68), with appreciable amounts of Na 2O and K 2O comparable to pyrope synthesized at 5GPa. The extremely high K 2O contents of K-rich augite micro-inclusions suggest non-equilibrium with the parental magma, whereas the other K-rich clinopyroxenes are similar to K-clinopyroxenes produced at 5–6GPa. K-clinopyroxene and garnet in mafic microgranular enclaves suggest that lamprophyric magma started its crystallization at upper mantle conditions, and chilled clinopyroxenes with measurable amounts of K 2O are taken as evidence that co-mingling began still at mantle pressures.